The complexity of vibrator baseplate-ground interaction measured with a thin-film pressure pad and a downhole tool - Dean, Tim; Vermeer, P.; Laycock, M.; Tulett, J.; Lane, D. (2015)
When a seismic hydraulic vibrator sweeps, it emits the signal we desire as well as a series of harmonics due to the non-linear behaviour of the hydraulic system and the baseplate-earth contact. The phase of the fundamental component of the transmitted signal also varies significantly from that of the pilot, which results in distortion of the Klauder wavelet. If we could record a more accurate estimate of the transmitted signal we could improve the signal itself (through the feedback loop of the vibrator's controller) and/or reduce its effects during processing. In this paper we show that the pressure distribution beneath the baseplate is more complex than previously thought but that thin-film pressure pads are a promising method for measuring the signature of a vibrator.